The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1111/jvim.13928
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy and Precision of Noninvasive Blood Pressure in Normo‐, Hyper‐, and Hypotensive Standing and Anesthetized Adult Horses

Abstract: BackgroundBlood pressure is relevant to the diagnosis and management of many medical, cardiovascular and critical diseases. The accuracy of many commonly used noninvasive blood pressure (NIBP) monitors and the accuracy of NIBP measurements in hypo‐ and hypertensive standing horses has not been determined.Hypothesis/ObjectivesThe objective of this study was to investigate the accuracy of an oscillometric BP monitor in standing horses before and during pharmacologically induced hyper‐ and hypotension and to comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
36
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 30 publications
9
36
0
Order By: Relevance
“…This is comparable to results of an early study where another monitor was evaluated in a similar study setting in horses (Branson 1997). The more recent studies using different oscillometric devices similarly showed an underestimation of MAP, SAP and DAP (Tünsmeyer et al 2015, Drynan et al 2016, Heliczer et al 2016, Olsen et al 2016). …”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…This is comparable to results of an early study where another monitor was evaluated in a similar study setting in horses (Branson 1997). The more recent studies using different oscillometric devices similarly showed an underestimation of MAP, SAP and DAP (Tünsmeyer et al 2015, Drynan et al 2016, Heliczer et al 2016, Olsen et al 2016). …”
Section: Discussionsupporting
confidence: 84%
“…have been evaluated revealing various results concerning the reliability of the different methods in different species (Riebold andEvans 1985, Bailey et al 1994). Oscillometric blood pressure measurement is commonly used in human and small animal medicine and several non invasive blood pressure monitors have been evaluated in standing or anaesthetised horses recently (Hatz et al 2015, Tünsmeyer et al 2015, Drynan et al 2016, Heliczer et al 2016, Olsen et al 2016 In the present study, overall the non-invasive blood pressure measurement underestimated MAP, SAP and DAP compared to the invasive measurement. In the medical field, European recommendations define 5 mmHg as very accurate, 6 -10 mmHg as slightly inaccurate, 11-15 mmHg as modera- tely inaccurate and >15 mmHg as very inaccurate (O'Brien et al 2002).…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…The mean SAP, DAP, MAP, and HR recorded for the MR and control groups in our study were similar to the reference values reported in the veterinary medical literature using an ultrasonic blood flow detector technique and an oscillometric method . Although PP of healthy horses is only specifically reported in a single paper, reference values for PP can be deduced from other reported SAP and DAP values obtained in healthy horses and were similar to those found in our control horses . Correction for tail height above heart base is necessary to evaluate the accuracy of NIBP measurements of SAP, DAP, and MAP among different sized horses but is redundant when assessing changes in PP, because both SAP and DAP will change by the same magnitude in a given horse.…”
Section: Discussionmentioning
confidence: 99%
“…Blood samples were collected at 8 am daily for determination of packed cell volume (PCV), total protein (TP) concentration, and serum biochemical profiles. Mean arterial pressure (MAP) was measured with a tail cuff using an oscillometric monitor device (SurgiVet Advisor [Smiths Medical, Norwell, Massachusetts]) as previously described . Mean arterial pressure was measured daily at T = 0 (before drug administration), and 1, 5, and 9 hours after drug administration.…”
Section: Methodsmentioning
confidence: 99%